2004
DOI: 10.1088/0305-4470/37/3/022
|View full text |Cite
|
Sign up to set email alerts
|

Number of quantal resonances

Abstract: Based on extraction of resonances from quantal time delay, a theorem relating quantal time-delay and the number of resonances below a certain energy is proved here. Several illustrations from quantum mechanics, neutron reflectometry and hadron resonances are presented.PACS numbers: 03.65.NkPhysics of weakly-bound systems and resonances has been of great interest for the important role it plays in nuclear and particle physics. In particular, deriving reliable information about unstable and short-lived states le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…This is a very important result as it immediately implies that the integral provides quantization condition for resonances. This explains all the recent results [9,10,11,12] where resonances in non-relativistic quantum mechanical problems , in neutron reflectometry, and in particle physics are reproduced by studying time-delay as a function of energy. Thus, we have shown that quantization (1) is connected to adiabatic invariance, and the correspondence with the phase space volume is established.…”
supporting
confidence: 71%
See 3 more Smart Citations
“…This is a very important result as it immediately implies that the integral provides quantization condition for resonances. This explains all the recent results [9,10,11,12] where resonances in non-relativistic quantum mechanical problems , in neutron reflectometry, and in particle physics are reproduced by studying time-delay as a function of energy. Thus, we have shown that quantization (1) is connected to adiabatic invariance, and the correspondence with the phase space volume is established.…”
supporting
confidence: 71%
“…We now focus on an individual quantum resonance and the phase space scenario associated with it. Let us observe that the resonances have more and more width as they occur at higher and higher energies, thus having lesser and lesser lifetimes [9]. Understanding that the energy-dependent mean lifetime is found from time-delay, this situation is the quantum analogue of the adiabatic invariance of product of energy and time-period of an adiabatically perturbed simple pendulum.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…2. The autoionization process does not occur instantly as the electron has to move from the interaction regime to an interaction free regime, which introduces a time delay because of the difference between the density of states of the two regions [27]. The energy-integral of time delay is an adiabatic invariant in quantum scattering theory and it provides a quantization condition for resonances [28].…”
mentioning
confidence: 99%